Experiencing loneliness by young people with different life variants - T. S. Pukhareva; A. G. Shisheva; E. I. Tur (Вестник университета)
The article presents the results of studying the experience of loneliness by young people who choose different life variants. The purposes of the study are aimed at generalising ideas about this phenomenon, at popularisation and development of scientific ideas on individual life variants in modern society for their subsequent use in psychological counseling practice and psychotherapy. The work also implies an empirical analysis and identification of the occurrence features. The “Differential questionnaire of loneliness experience” by E.N. Osin and D.A. Leontev and the «Actual life variant» technique by A.G. Shisheva were used as diagnostic tools. It is shown that the experience of loneliness by young people contributes to self-knowledge, self-development and the ability to establish trusting relationships. The most common life variants among young people are identified: “life as a preface” and “life by the rules”. It is stated that to study real life models of contemporary people in connection with other psychological realities is a promising line of researches.